DYNAMICS OF GOSLINGS’ LIVE WEIGHT AT AMIDOSTOMOSIS OF GEESE - Mykhailiutenko, S.; Zhulinska, O. (Scientific Progress & Innovations, 2021)
In comparison with mammals, the intensity of metabolism in waterfowl is much higher. In the process of evo-lution, they have developed the digestive system that is able to digest feed quickly, so it has significant differences in the structure: the stomach consists of two sections. The glandular stomach contains a huge number of cells that secrete both pepsinogen and hydrochloric acid. The function of the gizzard stomach is aimed at chemical and physical splitting of food. The latter is achieved as a result of vigorous muscle contractions and the presence of hydrolytesDigestive organs’ growth rates depend on the age, breed, conditions of keeping, feeding and health of the waterfowl. In their turn, helminthes, localized in the stomach and intestines, adversely affect their morpholog-ical and functional state and the organism as a whole. Therefore, the quality of meat and egg-laying, productivity of domestic waterfowl are reduced. Pathogenic parasites that are significantly common among domestic geese are the nematodes of Amidostomum anseris species (Zeder, 1800), which are localized in the stomach. The aim of the study was to establish the peculiarities of amidostomosis pathogen localization and the effect of nematodes on the dynamics of goslings’ live weight. The work was conducted on 16 geese of Gorkivska breed, which were kept on a private peasant farm of Poltava region. The diagnostic study was performed by the method of Yevstafieva V. O. and Mykhailiutenko S. M. (2012). The average daily weight gain of goslings was determined experimentally. It has been found that this indicator for the period of growing made 26.00 g in healthy goslings, and 23.46 g in the infected ones. It has been determined that the weight of the stomach glandular part in diseased goslings made 9.92±0.28 g. The average weight of the gizzard part was 145.65±2.31 g. The studies have shown that the main amount of amidostomosis pathogens were registered in the gizzard part of the stomach, namely in the tendon mirror area and in the areas of cranial and caudal blind pouches. At the same time, a significant amount of amidostomes were localized in the intermediate zone – zona intermedia. Mechanical and toxic effects of nematodes of Amidostomum anseris species on the gizzard stomach led to hemorrhagic-necrotic processes.